Optimization of Early Childhood Motor Development (AUD) through Interactive Games at PAUD and Bethel Kindergarten Sentani - Tasijawa, Riski; Ugadje, Evelin F; Pattipeiluhu, Krislina; Wangguway, Yustinus; Kadio, Yarsenita; Rorimpandey, Enjeli; Suwarni, Maria T (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Community service activities conducted by the Department of Early Childhood Christian Education (PKAUD) at STAKPN Sentani aim to enhance early childhood motor skills at PAUD and TK Bethel Sentani through interactive games. These activities include coconut shell stilts (egrang batok kelapa), role-playing with the theme of